Design(er) leadership in large corporations - Santos, José Manuel Fernandes dos (2021)
While there are those that believe the chief design officer is a growing phenomenon, and respected companies like McKinsey have stepped into the arena and provided very important data and insights attesting the importance of design, evidence seems to suggest that design leadership at the highest level in large corporations is still rare and that there aren’t many trained designers in those positions. When we started this journey in 2017, we articulated the following question: Why aren’t there more designers in the CSuite of F50 corporations? According to publicly available data, there were less than a handful formally educated designers (design, art, architecture) in the F50 reporting to the CEO, now in 2020 there is 1. Are we progressing towards design(er) leadership in large corporations, or perhaps regressing? Can we say that the decade of 2010-20 that saw some progress in this domain will be matched by a new decade of more design(er) leadership, or has design been so deeply engrained in corporations through successful design thinking initiatives that design will be in the hands of everyone and design leadership in the hands of traditional leaders in different domains, not with designers? This research and doctoral thesis attempts to shed some light on what might the insights impacting this reality. It includes the results of various data collection efforts, among them a survey done with large corporations’ executives, another with senior/ mid-career designers working in large companies, and the result of personal conversations with more than 30 professionals with experience and credible point of view on the topic. The thesis attempts to connect the data and provide insights on the state of design(er) leadership in large corporations, and provides insights that map this reality, while providing a meta-model for those designers, and others interested in changing it.